Launching Export Accelerations in Latin America and the World - Cerra, Valerie; Tesfaye Woldemichael, Martha (IMF working paper ;, 2017)
This paper investigates the determinants of sustained accelerations in goods and services exports. Strong predictors of export takeoffs include domestic and structural indicators such as lower macroeconomic uncertainty, improved quality of institutions, a depreciated exchange rate, and agricultural reforms. Lower tariffs, participation in global value chains and diversification also contribute to initiating export accelerations. The paper also finds heterogeneity, with somewhat different triggers for Latin America and the Caribbean, as well as for goods and services. Finally, despite the lack of a robust effect on output, export surges tend to be associated with lower post-acceleration unemployment and income inequality.